2017
DOI: 10.1016/j.aller.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrent wheezing in the first year of life in the city of Córdoba, Argentina

Abstract: It is known that persistent respiratory problems in children due to low socioeconomic status is a risk factor for wheezing, pneumonia and could be a determining factor in the prevalence and severity of RW in infants. Research suggests that there are areas for improvement in the implementation of new educational strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…The relation between persistent respiratory problems and socioeconomic status has been remarked in many studies. 39,40 However, as the families in general did not want to say their actual level of income, we could not evaluate the economic status directly. We tried to indirectly evaluate according to their educational level.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between persistent respiratory problems and socioeconomic status has been remarked in many studies. 39,40 However, as the families in general did not want to say their actual level of income, we could not evaluate the economic status directly. We tried to indirectly evaluate according to their educational level.…”
Section: Discussionmentioning
confidence: 99%
“…Teijeiro et al [25] studied the risk factors of recurrent wheezing in the first year of life and found that frequent airway infections and bronchiolitis in the first three months of life ( > 6) and passive smoking were risk factors and high socioeconomic status was a protective factor. In 2017 Bao et al [3] reported a meta-analysis about risk factors for predicting asthma in preschool children.…”
Section: Asthma Group ( %) Non-asthmatic Group ( %) Aor (95 % Ci) Pmentioning
confidence: 99%
“…Окрім того, на тлі змін імунітету у ДЧХ мікробна флора слизової оболонки (СО) верх ніх дихальних шляхів (ВДШ) починає теж змінюватися із заміщенням облігатної мікро флори, яка колонізує слизові оболонки у здо рових дітей, на патогенні мікроорганізми. Тен денція до зведення мікрофлори СО ВДШ до монокультури також може сприяти розвит ку частих ГРЗ у дітей [12,13,14].…”
Section: тв починок 1 лв стамболі 2 лв сліпачук 1 ов жуunclassified